How Big is the Role of Loneliness on Fear of Missing Out? : A Study on Teenage K-Pop Fans - Arizka, Rahmi; Khotimah, Husnul; Supraba, Dellawaty (Journal of Health and Behavioral Science, 2024)
The high use of social media can lead to fear of missing out (FoMO) among adolescent K-pop fans because the desire to connect with individuals is relatively high. One factor that influences Fear of Missing Out in teenage K-pop fans is loneliness. This research was conducted to determine the effect of Loneliness on FoMO in K-pop fans. The subjects in this study were teenage K-pop fans with a purposive sampling technique. Subjects were taken as many as 100 subjects from the total infinite population. This study uses quantitative methods with psychological loneliness scales and Fear of Missing Out (FoMO). The loneliness scale has 58 items with a reliability value of 0.863. The FoMO scale has 26 items with a reliability value of 0.947. The analysis test uses the assumption test and simple linear regression hypothesis test. The results of this study indicate a significant effect of loneliness on the FoMO of teenage K-pop fans, with a significant value of 0.005. The magnitude of the influence of loneliness is 7.8% on FoMO in teenage K-pop fans.